A quasi‐linear piezoelectric strain behavior of [001] textured rhombohedral PMN–24%PT ceramic. Issue 11 (19th July 2020) - Hao, Mengmeng; Fan, Guifen; Cai, Wei; Zhang, Qianwei; Zeng, Fangfang; Wen, Yue; Wang, Yanjiong; Chen, Xin; Wang, Fei; Lou, Yihui; Lv, Wenzhong
Abstract: Highly textured (1–x)Pb(Mg1/3 Nb2/3 )O3 ‐xPbTiO3 (PMN–xPT) piezoelectric ceramics were fabricated. It was found that [001] textured rhombohedral PMN–24%PT ceramic exhibited a quasi‐linear piezoelectric strain behavior with low hysteresis. The strain hysteresis of PMN–24%PT ceramic was reduced from 22.5% to 9% at 30 kV/cm using the texture method. Accurate displacement was generated by DC field using textured PMN–24%PT ceramic. The domain configurations in textured PMN–xPT ceramics were figured out using the chemical etching method. It was demonstrated that the quasi‐linear and low‐hysteretic strain behavior was due to a fixed domain configuration. We predict that the textured PMN–24%PT ceramic will facilitate the development of low‐voltage driving piezoelectric actuators with high precision. Abstract :